Influence of Lifestyle and Prices Regarding Purchasing Decisions at UD Putra TS Majalengka - Wawan Yuswanto; Emi Amelia; Dea Siska Paramita (Politeknik Mardira Indonesia, 2024)
Lifestyle is one of the driving factors for someone to make purchasing decisions. Apart from lifestyle, price and product quality are also influences in purchasing decisions. So it is very important for marketers to understand and study consumer behavior to create sales strategies. This research aims to determine the influence of lifestyle and price both partially and simultaneously on purchasing decisions at UD Putra TS Majalengka.The method used in this research is a descriptive and verification research method with a sample of 96 people who are consumers who come to the UD Putra TS Majalengka, and uses multiple linear regression analysis to determine the mathematical model, product moment (Pearson) correlation analysis , to calculate the level of the closeness of the relationship of determination analysis to determine the effect. To make data processing easier, the author uses SPSS for window software version 25.0.The results obtained show that lifestyle and price have a very strong and positive relationship with purchasing decisions, namely with a correlation of 0.801, while the magnitude of the influence on purchasing decisions is 64.2% as measured using the coefficient of determination formula. based on hypothesis testing, lifestyle and price together have a positive and significant effect on purchasing decisions. Because the value of Fcount (83.432) > Ftable (3.09), so H0 is rejected and Ha is accepted.